Paracanoe: particularities of functional classes in the structuring of the sports' training - Luiz Gustavo Teixeira Fabricio dos Santos; Maria Florencia Sierra; Luis Felipe Correia Castelli de Campos; Edison Duarte; Cristian Rocha Luarte; Paulo Cesar Montagner; Joao Paulo Borin (Universidad Católica del Maule, Facultad de Ciencias de la Educación, 2023)
The performance of paracanoistsis characterized by the ability of the athlete to advance at maximum speed, through a technically optimal paddling motion. It`s important to consider that in the case of para-athletes, the application of forces towards paddling is compromised by physical deficiencies. Thus, this study aims to assess the performance of athletes in the KL1, KL2 and KL3 sport classes, during a paralympicparacanoe event. The sample was composed of athletes from the Brazilian male paracanoe team, with a representative of each sport class: KL1, KL2, KL3 For performance analysis, we used a kayak ergometer (KayakPro®, Miami Beach, FL, USA) to simulate a 200-meter trial, during Rio 2016 Paralympic Games Road. The variables were evaluated: time trial, stroke frequency, mean speed, number of strokes, stroke length, stroke index, and power. According to results: I) the athlete KL3 had the lowest number of strokes, the longest stroke length and the highest stroke rate index; II) the athlete KL1 had the highest number of strokes, the lowest stroke length and the stroke rate index. This study puts into perspective the distinct characteristics of a paracanoe trial, analyzed in consideration to each sport class.